A = n4.(n2 - 1) + 2n2.(n+1) = n4.(n+1).(n-1) + 2n2.(n + 1) = n2(n + 1). (n2.(n -1) + 2)
= n2(n + 1).(n3 - n2 + 2) = n2(n + 1).(n3 + 1 + 1 - n2) = n2(n + 1).(n +1). (n2 - n + 1 - n + 1) = n2( n + 1)2.(n2 - 2n + 2)
Với n > 1 => n2 - 2n + 1 < n2 - 2n + 2 < n2
=> (n - 1)2 < n2 - 2n + 2 < n2
(n - 1)2 ; n2 là 2 số chính phương liên tiếp => n2 - 2n + 2 không thể là số chính phương
=> A không là số chính phương
mình ko biết
`n6 - n4 + 2n3 + 2n2`
`= n2 . (n4 - n2 + 2n +2)`
`= n2 . [n2(n - 1)(n + 1) + 2(n + 1)]`
`= n2 . [(n + 1)(n3 - n2 + 2)]`
`= n2 . (n + 1) . [(n3 + 1) - (n2 - 1)]`
`= n2. (n + 1)2 . (n2 - 2n + 2)`
Với `n ∈ N, n > 1` thì` n2 - 2n + 2 = (n - 1)2 + 1 > (n - 1)2`
Và `n2 - 2n + 2 = n2 - 2(n - 1) < n2`
Vậy `(n - 1)2 < n2 - 2n + 2 < n2`
`=> n2 - 2n + 2` không phải là một số chính phương.